Sistem Manajemen Kelas Menggunakan K-Means Clustering untuk Pengelompokan Kelas Unggulan pada Sekolah Dasar Negeri Neglasari 3 - Anggraini, Fitri; Suprapta, Imam; Warno, Warno; Fahrezi, Hafid (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to develop and analyze a classroom management system using K-Means Clustering at SD Negeri Neglasari 3. The system is designed to group outstanding classes objectively, efficiently, and transparently based on students' academic achievements. The system is designed to streamline the data processing of students in the grouping of elite classes, which currently still relies on manual processes. The system development method used is the waterfall method, consisting of the following stages: Requirement Analysis, Design, Implementation, Testing, and Maintenance. The system is built using the Hypertext Preprocessor (PHP) programming language and the MySQL database. To test the developed system, several methods were used, including black-box testing, User Acceptance Test (UAT), time comparison tests (pre-test and post-test), and the distribution of satisfaction questionnaires to 10 teachers as respondents. The research results showed that black-box testing and User Acceptance Test validation were 100% successful. Additionally, the developed system demonstrated a significant improvement in task completion time efficiency for class grouping, increasing by 80.63% compared to manual methods. The questionnaire responses yielded a score of 4.49 out of 5. Thus, the research findings confirm that the developed system is a valid solution for objectively and efficiently grouping elite classes